2006
DOI: 10.1063/1.2164431
|View full text |Cite
|
Sign up to set email alerts
|

Actively tuned and spatially trapped polaritons

Abstract: We report active tuning of the polariton resonance of quantum well excitons in a semiconductor microcavity using applied stress. Starting with the quantum well exciton energy higher than the cavity photon mode, we use stress to reduce the exciton energy and bring it into resonance with the photon mode. At the point of zero detuning, line narrowing and strong increase of the photoluminescence are seen. By the same means, we create an in-plane harmonic potential for the polaritons, which allows trapping, potenti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 17 publications
0
59
0
Order By: Relevance
“…The enhanced coherence has motivated basic investigations of micro-optical parametric oscillators [4] as well as ultrafast optical amplifiers [5]. Successful tuning of MC polaritons, without changing their dimensionality, has been demonstrated using static electric [6] and strain fields [7]. Conversely, the static reduction of polariton dimensionality using lithographically defined structuring has also been reported [8][9][10][11].…”
Section: Phonon-induced Polariton Superlatticesmentioning
confidence: 99%
“…The enhanced coherence has motivated basic investigations of micro-optical parametric oscillators [4] as well as ultrafast optical amplifiers [5]. Successful tuning of MC polaritons, without changing their dimensionality, has been demonstrated using static electric [6] and strain fields [7]. Conversely, the static reduction of polariton dimensionality using lithographically defined structuring has also been reported [8][9][10][11].…”
Section: Phonon-induced Polariton Superlatticesmentioning
confidence: 99%
“…This produces a shallower confinement than for micropillars but the polariton energy spectrum is clearly discretized. Another approach is to create a trap in real space by applying a local stress, with a tip pushing on the back side of a cavity sample [29]. In this case, polariton trapping has been observed in this local energy minimum, but the energy spectrum remains a quasi-continuum.…”
Section: Demonstration Of the Strong Coupling Regimementioning
confidence: 99%
“…Triggered by a series of remarkable experiments, [1][2][3][4] during the last decade one observes a rapidly growing interest in the study of highly populated (macroscopic) exciton-polariton states, which are also identified as quasiparticle Bose-Einstein condensates (BECs). 5,6 Unlike the atomic BECs, the condensates emerging from the interaction of light and matter are nonconservative and exist due to the intense energy exchange with the laser pump beam, balanced by relatively strong losses of excitons and photons arising, for example, due to material and cavity imperfections.…”
Section: Introductionmentioning
confidence: 99%